Peran Zakat dalam Pertumbuhan Ekonomi di Provinsi Lampung (Studi pada Baznas Kota Bandar Lampung) - Moh. Bahrudin; Agus Kurniawan; Suhendar Suhendar (ITB AAS INDONESIA Surakarta, 2022)
This study was conducted to determine and analyze the role of zakat in economic growth in Lampung Province. The method used in this study is a descriptive method with a qualitative approach. The data used in this study are primary and secondary data. The population in this study is the mustahiq zakat in Bandar Lampung City. The sample in this study was the mustahiq recipients of the productive zakat program in Bandar Lampung City with purposive sampling technique. The primary data in this study were obtained from the results of filling out questionnaires and interviews. Secondary data in the form of BAZNAS report documentation Bandar Lampung City. The primary data questionnaire used has been tested for validity and reliability. The collected data is analyzed by referring to qualitative data analysis techniques which include 1) data collection, 2) data reduction, 3) data presentation and 4) drawing conclusions. The results of this study generally explain that in general zakat plays a role in encouraging economic growth. The roles of zakat include 1) as an additional source of income, 2) additional productive capital and 3) additional education and health costs.